Identifying the Key Genes in Mouse Liver Regeneration After Partial Hepatectomy by Bioinformatics Analysis and in vitro/vivo Experiments - Zhao, Jian; Yu, Shi-Zhe; Cai, Qiang; Ma, Duo; Jiang, Long; Yang, Ling-Peng; Yu, Zhi-Yong (Frontiers in Genetics, 2021)
Background: The liver is the only organ that can completely regenerate after various injuries or tissue loss. There are still a large number of gene functions in liver regeneration that have not been explored. This study aimed to identify key genes in the early stage of liver regeneration in mice after partial hepatectomy (PH). Materials and methods: We first analyzed the expression profiles of genes in mouse liver at 48 h and 72 h after PH from Gene Expression Omnibus database. Gene Ontology, and the Kyoto Encyclopedia of Genes and Genomes, and protein-protein interaction analysis were performed to identify key genes in liver regeneration. Finally, we validated key genes in vivo and in vitro. Results: We identified 46 upregulated genes and 19 downregulated genes at 48 h after PH, and 223 upregulated genes and 40 downregulated genes at 72 h after PH, respectively. These genes were mainly involved in cell cycle, DNA replication, and p53 signaling pathway. Among of these genes, cycle-related genes (CCNA2, CDKN1A, CHEK1, MCM5) and UBE2C were highly expressed in the residual liver both at 48 h and 72 h after PH. Furthermore, UBE2C knockdown not only caused abnormal expression of CCNA2, CDKN1A, CHEK1, and MCM5, but also inhibited transition of hepatocytes from G1 to S phase of the cell cycle in vitro. Conclusion: Mouse hepatocytes enter the proliferation phase at 48 h after PH. UBE2C may mediate cell proliferation by regulating or partially regulating CCNA2, CDKN1A, CHEK1, and MCM5.